Apartment Buildings Today - Broto, Carles, author 378942; Noden, Jay, editor 484670; George, William, 1948-, editor 234325 (Barcelona, SP. : Links International ; Garsington : Windsor [distributor], 2011)
Alvaro Siza, Neutelings & Riedijk, Bevk Perovic, Delugan Meissl and Eduardo Souto de Moura are among the distinguished architects whose work is featured in this collection. Centring on residential architecture, it considers the finest achievements of the world's most prestigious architects in recent times.